Analysis of Taxpayer Compliance and Audit in the Context of Taxation in Indonesia - Dea Putrima Sari Pasaribu; Galuh Tresna Murti; Nadya Yumna Putri; Anbiya Abdul Ghani (Jurnal Riset Perpajakan: Amnesty, 2023)
Indonesia is a state of law and the law is mandatory and must be obeyed, so one of the legal provisions in Indonesia is taxation, because taxes are fees imposed by the government to finance it. committing fraud will be subject to sanctions in the form of sanctions in the form of management sanctions, and criminal sanctions in confinement or confinement. the refund of tax overpayments also begins with the submission of a tax refund application, which is followed by an examination of the refund application by the DGT. This study aims to learn more about taxation procedures through various sub-discussions. This study adopts the literature research method to explore further related theories and previous research. in the written abstract: 1) Definition of tax audit 2) Purpose of tax audit 3) audit to test compliance 4) investigation for other purposes 5) tax assessment letter 6) tax billing letter 7) tax notification letter.